2022
DOI: 10.3390/agriculture12111797
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Humic Substances in Composts Comprised of Different Organic Source Material

Abstract: Reusing organic waste as fertilizer is one method to reduce the use of mineral fertilizers and minimize waste disposal in landfills. Regulations have been enacted for the processing of organic waste and for recycling end products, but the humic content of organic fertilizers has been neglected. We studied seven composts with different organic input materials and technologies. Humic substances (HSs) were detected in all composts. The total organic carbon in the HSs constituted 8.7 ± 0.1% (SD)–27.0 ± 0.2% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Humic substances (HS), including humic acid, fulvic acid, and humin, have great benefits in soil, like promoting nutrient uptake, and are correlated with the maturity of compost 32 . Zhu et al 33 , and Huang et al 34 have reported that the HA + FA (humic and fulvic acid) contents of compost obtained from dairy and pig manure with pre-treatment of initial materials were 6.7% and 20%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Humic substances (HS), including humic acid, fulvic acid, and humin, have great benefits in soil, like promoting nutrient uptake, and are correlated with the maturity of compost 32 . Zhu et al 33 , and Huang et al 34 have reported that the HA + FA (humic and fulvic acid) contents of compost obtained from dairy and pig manure with pre-treatment of initial materials were 6.7% and 20%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the E 365 / E 250 ratio for the evaluated samples indicate that the molecular size and degree of condensation of HSs depended mainly on the type of raw material from which the HSs were isolated, which is consistent with the conclusions about the degree of humification and points to the correlation between the degree of organic matter conversion and the molecular structure of the HSs, which were isolated from a given raw material. 53 55 Based on the comparison of the E 365 / E 250 values for the isolated humic extracts (HSP, HSL, HSP NaOH , and HSL NaOH ) with the samples purchased from Sigma-Aldrich (HA SIGMA and NaH SIGMA ), it can be observed that the HSs obtained in this study were characterized by lower condensation, which is caused by the presence of fulvic substances in the humic extracts, which are a fraction with a lower degree of condensation and molecular weight, compared to humic acids and humates. 56 , 57 The values of the last absorbance ratio determined in this study ( E 270 / E 400 ) for the samples analyzed indicated a higher carboxyl content in the samples extracted using ADESs.…”
Section: Resultsmentioning
confidence: 99%
“…Humic acids are the essence of organic matter and the active and important part, which is characterized by its amorphous colloidal nature [1]. One of the basic humic acids is (Humic acid) C 75 H 22 O 17 N 2 (COOH) 2 (OH) 6 (CO) 2 , which is characterized by the diversity of the size of its particles and the heterogeneity in terms of the details of its structural structure, and therefore the determination of the molecular weight of the particles is very complicated, most of the quantities of humic acids accumulate in the upper layer of the soil due to their association with calcium and manganese, which leads to their loss of portability [2]. Humic acids represent the most important part of the humus because of its high exchange capacity for positive ions.…”
Section: Introductionmentioning
confidence: 99%